Oxygen Vacancy Mediated Stabilization of Cubic Phase at Room Temperature and Resistive Switching Effect in Sm- and Dy-Doped HfO2 Thin Film - Kumar S.; Rath C. (My University, 2025)
Recently, binary transition metal oxide-based resistive random access memory (RRAM) has been attracted for future nonvolatile data storage devices. Herein, the structural evolution and resistive switching behavior of pristine and Sm- or Dy-doped hafnium oxide (HfO2) films of ≈60 nm deposited on p++-Si (100) substrates through electron-beam evaporation technique are systematically investigated. Although it is reported that 12 at% of Sm or 11 at% of Dy doped in HfO2 nanoparticles stabilize the high-temperature cubic phase at RT, herein, the stabilization of cubic phase after doping at most half of these dopant concentration is demonstrated. Furthermore, these films exhibit the bipolar switching behavior distinctive to RRAM device. Interestingly, the resistive switching characteristics are found to be of forming-free nature. To understand the switching behavior, different conduction models such as the Ohmic and Poole–Frenkel emission are used. The monoclinic to cubic phase transformation and resistive switching phenomenon are discussed in terms of the abundant formation of oxygen vacancies producing eightfold oxygen coordination to Sm3+ or Dy3+ ion evidenced from photoluminescence and X-ray photoelectron spectroscopy. The resistive switching mechanism through the formation of conducting filaments is pictorially illustrated in HfO2-based RRAM. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim